Effects of Disodium Hydrogen Phosphate Addition and Heat Treatment on the Formation of Magnesium Silicate Hydrate Gel - Phuong, Thi Nguyet; Vu, Thi Ngoc Minh (Engineering and Technology For Sustainable Development, 2021)
The formation of magnesium silicate hydrate gel is crucial in preventing magnesia aggregates from over hydrated during the construction of refractory castables since the presence of magnesium hydroxide diminish the mechanical properties of the material. This work aimed to investigate the accelerating effects of sodium hydrogen phosphate and heat treatment on the formation of magnesium silicate hydrate gel. Time-dependent pH of magnesia - silica fume slurries with and without sodium hydrogen phosphate addition and heat treatment was measured to verify the dissolution of MgO and magnesium silicate hydrate formation. The effects of sodium hydrogen phosphate were differentiable only at small added amounts, whereas heat treatment at 50 degrees Celsius performed noticeable acceleration. This observation could be applicable in molding to maintain the stability of basic refractory castables.